The Influence of Nutrition Management Education on Mothers Knowledge and Attitudes in Fulfilling Nutrition for Obese Pregnant Women - Syafitasari, Juanda; Putri, Poppy Siska; Afriannisyah, Entan (Universitas Airlangga, 2024)
Obesity is a high obstetric risk increasing the risk of maternal and fetal morbidity and death. Complications that can occurred in pregnant women with obesity are an increased risk of hypertension, gestational diabetes, spontaneous abortion, and postpartum hemorrhage. This research aims to determine the effect of nutritional management education on mothers knowledge and attitudes in fulfilling nutritional needs of obese pregnant women. The study used a quasi-experiment with a pre-test and post-test with a control group design. The sample in this study was 60 obese pregnant women who were divided into an intervention group and a control group, each with 30 respondents. The instruments used were observation sheets and nutritional management menu lists. Data analysis used the Mann-Whitney test with a significance level of p â‰¤ 0.05. The study showed a significant difference between knowledge (p-value=0.015) and mothers' attitudes towards fulfilling nutrition (p-value=0.011) before and after nutrition management education. Nutrition management education is critical to improving nutritional fulfilment for pregnant women.